2022
DOI: 10.11648/j.ijaas.20220801.17
|View full text |Cite
|
Sign up to set email alerts
|

Response of Different Fertilizer Levels on Grain Yield and Yield Components of Food Barley Varieties at Arsi Zone, Ethiopia

Abstract: A field experiment was conducted at Lemu-bilbilo wereda, Arsi Zone, Ethiopia, from June to December 2017/18 cropping season, with the aim of evaluating the optimal level of fertilizers for maximal production of food barley varieties on two farmer's site. Four levels fertilizer (RNP (100 kg/ha urea + 150 kg/ha DAP) (73N, 69 P 2 O 5 ), 150%RNP, 200%RNP and RNPS (100 kg/ha) (19 N 38 P 2 O 5 + 7S) and three food barley varieties (HB42, HB1307 and EH1493) were tested in Randomized complete Block Design replicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…A longer grain filling periods allow photosynthetic components to remain green improving grain filling and leading to good grain yield of post-anthesis assimilates which is important in cereals 11 ) and bit all the varieties studied. In line with this study, Lema et al 8 , Shimeles et al 5 and Birhanu et al 13 , reported that the highest mean grain yield was recorded from HB 1307 (2427.8, 5143 and 6764 kg haG 1 ) respectively and similarly variety Ageghehu was reported among the low yielders in both authors. This variety HB 1307 was also found to be among the high-yielder varieties in an experiment done in the Central Highlands of Ethiopia 14 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A longer grain filling periods allow photosynthetic components to remain green improving grain filling and leading to good grain yield of post-anthesis assimilates which is important in cereals 11 ) and bit all the varieties studied. In line with this study, Lema et al 8 , Shimeles et al 5 and Birhanu et al 13 , reported that the highest mean grain yield was recorded from HB 1307 (2427.8, 5143 and 6764 kg haG 1 ) respectively and similarly variety Ageghehu was reported among the low yielders in both authors. This variety HB 1307 was also found to be among the high-yielder varieties in an experiment done in the Central Highlands of Ethiopia 14 .…”
Section: Discussionsupporting
confidence: 82%
“…Despite releasing many varieties extension work on the promotion of improved varieties in the country has been very poor compared with that of bread wheat and maize 3 . Barley productivity is limited by poor soil fertility, frost, water logging, insect and leaf diseases, moisture stress, low-yielding varieties and, adequate agronomic practices 5 . These produce poor yields and have been practiced for centuries.…”
Section: Introductionmentioning
confidence: 99%